The Relationship between Parental Communication Patterns and Elementary School Students’ Learning Discipline - Lystia Nabilah; Lu’luil Maknun (Pusat Pengembangan Pendidikan dan Bakat Indonesia, 2024)
Student learning discipline is one of the crucial foundations in achieving optimal academic achievement, but discipline problems are still often found in the elementary school environment. This study aims to analyze the relationship between parental communication patterns and the learning discipline of fifth-grade students at Rawabuntu 01 State Elementary School. This study used a quantitative approach with a correlational design, involving 54 students as samples selected through the Slovin formula. Data were collected through questionnaires measuring parental communication patterns based on openness, empathy, support, positive attitude, equality, and learning discipline based on order, self-control, and concentration. The results showed a positive and significant relationship between parental communication patterns and learning discipline, with a correlation value of 0.468 and a contribution of 21.9%. Specific findings show that positive attitudes and parental support have the most significant influence, while communication openness still needs improvement.